Formação em psicologia para atuação crítica em educação básica pública: contribuições dos estágios acadêmicos - Oliveira, Priscila da Silva (2020)
Although the relationship between Psychology and Education has always been present in the history of Brazilian Psychology, the need to discuss this relationship and the actions in this field is still current. Since the late 1970s, criticism has been made of individualizing and pathologizing practices and, to overcome them, many new models have been proposed. Psychology training, currently based on the "Diretrizes Curriculares Nacionais (DCNs)" - in a free translation "the National Curriculum Guidelines", also undergoes changes in order to encourage the training of new psychologists who are prepared to consider individuals in their multiple determinations, to break the theory versus practice dichotomy and understand that the problematization of practice is necessary to the process of theoretical formation. In the DCNs, it is proposed that the internships enable training closer to praxis, supporting the development of ethical and professional responsibility and a critical attitude. Therefore, in the present research, the aim was to understand whether academic internships are recognized by students as a resource for training in Psychology that prepares them for critical performance in public Basic Education. Socio-historical psychology was used as a theoretical-methodological reference because it is a critical perspective in psychology, which considers an individual as an active, social and historical subject and is critical to the internal / external, natural / social, individual-society dichotomies. The analysis was based on interviews with psychology students from PUC-SP who were taking curricular internships in public schools, two meaning centres can be reached: 1. From the scholar clinic to the broader institutional insertion; 2. The possibility of a new commitment: the internship experience. We note the importance of the intention to train psychologists to act critically, the importance of internships and the contributions of internships in public education. It is concluded that the theoretical-practical training allows the deconstruction of traditional concepts of psychology towards a critical view of Educational Psychology